2009
DOI: 10.1523/jneurosci.4829-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for FGF2 as an Endogenous Inhibitor of Anxiety

Abstract: Human postmortem studies have demonstrated that fibroblast growth factor-2 (FGF2) expression is decreased in the brain of depressed individuals. It remained unclear, however, whether this is a consequence of the illness or whether FGF2 plays a primary role in the control of mood and emotions. In this series of studies, we first ask whether endogenous FGF2 expression correlates with spontaneous anxiety, a trait associated with vulnerability to severe mood disorders in humans. This is tested in two genetically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
175
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(193 citation statements)
references
References 45 publications
(57 reference statements)
18
175
0
Order By: Relevance
“…For example, endogenous hippocampal FGF2 expression correlated with spontaneous open arm time on the EPM in outbred rats (14). Moreover, animals that naturally exhibit high anxiety-like behavior have low levels of hippocampal FGF2 (12,13). In contrast, we have demonstrated here that ten days of social defeat stress up-regulates hippocampal FGF9 expression while decreasing body weight and social interactions, correlates of increased depression-like behavior.…”
Section: Fgf9 Expression Mediates Affect In An Animalmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, endogenous hippocampal FGF2 expression correlated with spontaneous open arm time on the EPM in outbred rats (14). Moreover, animals that naturally exhibit high anxiety-like behavior have low levels of hippocampal FGF2 (12,13). In contrast, we have demonstrated here that ten days of social defeat stress up-regulates hippocampal FGF9 expression while decreasing body weight and social interactions, correlates of increased depression-like behavior.…”
Section: Fgf9 Expression Mediates Affect In An Animalmentioning
confidence: 57%
“…Moreover, administration of antidepressants and anxiolytics induced FGF2 expression (9-11), and recent studies suggested that this induction is necessary for the effectiveness of the antidepressants (8). Paralleling the human depression studies, hippocampal FGF2 was basally decreased in high-anxiety animals, but chronic administration in adulthood (12) or a one-time administration of FGF2 during early development (13) alleviated their anxious phenotype. Additionally, anxiety-like behavior in outbred rats was increased by knocking down FGF2 in the dentate gyrus (DG) of the hippocampus (14).…”
mentioning
confidence: 96%
“…For example, FGF2 has previously been trialed in humans as a potential inducer of angiogenesis (Lederman et al, 2002). Furthermore, recent research has demonstrated that chronic administration of FGF2 reduces anxiety and depressive-like behavior in rats (Perez et al, 2009;Turner et al, 2008). However, we are the first to propose its use as a novel pharmacological adjunct to exposure therapy (Graham and Richardson, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…The bLR-HR rats were generated from our in-house breeding colony, where the bLR/bHR lines have been maintained for several generations (35). On the basis of the locomotor activity, bHR and bLR rats of our breeding colony were screened as described (30). Peripheral neonatal FGF2 administrations were performed as previously described on both bHRs and bLRs (28).…”
Section: Methodsmentioning
confidence: 99%
“…Its direct chronic administration was anxiolytic and antidepressant in rodents (25) and the silencing of endogenous hippocampal FGF2 using short-hairpin RNA increased anxiety-like behavior in outbred rats (26,27). Our bLRs, which exhibit higher anxiety and depression behaviors, have lower basal levels of FGF2 mRNA in HC and nucleus accumbens (NAcc) (28,29), and an environmental manipulation during adulthood that decreases anxiety behavior induces FGF2 expression selectively in these bLRs (30). Moreover, early-life FGF2 administration selectively decreases anxiety in bLRs throughout life (28).…”
mentioning
confidence: 93%